Importance of using field spectroscopy to support the satellite remote sensing for underground structures intended for security reasons in the eastern Mediterranean region - Melillos, George; Themistocleous, Kyriacos; Papadavid, George; Agapiou, Athos; Prodromou, Maria; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2016)
© 2016 SPIE. Underground structures can affect their surrounding landscapes in different ways such as soil moisture content, soil composition and vegetation vigor. Vegetation vigor is often observed on the ground as a crop mark; a phenomenon which can be used as a proxy to denote the presence of underground and not visible structures. This paper presents the results obtained from field spectroradiometric campaigns at 'buried' underground structures in Cyprus. A SVC-HR1024 field spectroradiometer was used and in-band reflectances were calculated for the Landsat 5 TM medium spatial resolution satellite sensor. A number of vegetation indices such as NDVI, SR and EVI were obtained while a 'smart index' was developed aiming for detection of underground military structures by using existing vegetation indices or other in-band algorithms. In this study, test areas were identified, analyzed and modeled. The areas have been analyzed and tested in different scenarios, including: (a) the 'natural state' of the underground structure (b) the different type of crop over the underground structure and imported soil (c) the different types of non-natural material over the underground structure. A reference target in the nearby area was selected as a baseline. Controllable meteorological and environmental parameters were acquired and monitored.
Keywords: EVI; military underground structures; NDVI; Remote sensing; spectroscopy; SR; vegetation indices